PENGARUH PENDAPATAN ASLI DAERAH DAN DANA ALOKASI UMUM TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL PADA PEMERINTAH KABUPATEN NIAS BARAT PERIODE 2016-2021 - Gulo, Vivin Tri Indawati; Purba, Imelda Rimenda (Jurnal Ilmiah Akuntansi (JIMAT), 2022)
This study aims to examine the effect of Regional Original Revenue (PAD), General Allocation Fund (DAU), on the Capital Expenditure of West Nias Regency. So that the sample is 18 where (PAD 6, DAU 6, Capital Expenditure 6) from 2016-2021. The research method used is descriptive quantitative using secondary data sourced from the regional government budget report of West Nias Regency in 2016-2021. The data analysis technique used is multiple linear regression statistical analysis. The analysis process carried out first is descriptive statistics, classical assumption tests, and hypothesis testing. The results of this study partially show that Regional Original Income has no effect on Capital Expenditures and the results of the study simultaneously show that the General Allocation Fund has no significant effect on Capital Expenditures. Keywords: Regional Original Revenue (PAD), General Allocation Fund (DAU), Capital Expenditure